Sorption isotherms and thermodynamic properties of grated Parmesan cheese - Faria Freitas, Mirian Luisa [UNESP]; Polachini, Tiago Carregari [UNESP]; Souza, Ana Cristina de; Telis-Romero, Javier [UNESP] (Wiley-Blackwell, 2016)
This study focuses on isotherms, isosteric heat of sorption and enthalpy-entropy mechanism of water sorption of grated Parmesan cheese at simulating conditions of storage and drying processes. Isotherms were determined by gravimetric method using different saturated salt solutions. Samples were submitted to different temperatures, and several models were used to fit experimental data, GAB and modified GAB being those which best represented experimental data in all temperature ranges. The isosteric heat of sorption was calculated by Clausius-Clapeyron equation, and higher values of integral isosteric sorption heat were verified for storage temperatures. Besides it, both conditions showed higher values of sorption heat corresponding to low water content. This phenomenon was supported by the enthalpy-entropy compensation study, which demonstrated a higher spontaneity of water sorption for storage temperatures, confirming that the lower the water content of food products is, the stronger the intermolecular bonds of water are.
Keywords: Enthalpy-entropy; GAB equation; isotherms; mathematical modelling; moisture content; Parmesan cheese; sorption isosteric heat; thermodynamic properties; water activity